Neo-Victorian villains : adaptations and transformations in popular culture - Poore, Benjamin, 1971- (Brill, 2017)
Neo-Victorian Villains is the first edited collection to examine the afterlives of such Victorian villains as Dracula, Svengali, Dorian Gray and Jekyll and Hyde, exploring their representation in neo-Victorian drama and fiction. In addition, Neo-Victorian Villains examines a number of supposedly villainous types, from the spirit medium and the femme fatale to the imperial 'native' and the ventriloquist, and traces their development from Victorian times today. Chapters analyse recent theatre, films and television - from Ripper Street to Marvel superhero movies - as well as classic Hollywood depictions of Victorian villains. In a wide-ranging opening chapter, Benjamin Poore assesses the legacy of nineteenth-century ideas of villains and villainy in the twentieth and twenty-first centuries. Contributors are: Sarah Artt, Guy Barefoot, Jonathan Buckmaster, David Bullen, Helen Davies, Robert Dean, Marion Gibson, Richard Hand, Emma James, Mark Jones, Emma V. Miller, Claire O'Callaghan, Christina Parker-Flynn, Frances Pheasant-Kelly, Natalie Russell, Gillian Piggott, Benjamin Poore and Rob Welch.
Includes index.
Keywords: Villains in literature.; Villains in motion pictures.; Characters and characteristics in literature.; Characters and characteristics in motion pictures.; English literature -- Adaptations -- History and criticism.; English literature -- 19th century -- Influence.; Méchants dans la littérature.; Méchants au cinéma.; Personnages au cinéma.; Littérature anglaise -- 19e siècle -- Influence.; 1800-1899.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Characters and characteristics in literature; Characters and characteristics in motion pictures; English literature -- Influence; Villains in literature; Villains in motion pictures; 1800-1899; Criticism, interpretation, etc.